Reliable nanofabrication of single-crystal diamond photonic nanostructures for nanoscale sensing - Radtke, Mariusz; Nelz, Richard; Slablab, Abdallah; Neu, Elke (Micromachines, 2019)
In this manuscript, we outline a reliable procedure to manufacture photonic nanostructures from single-crystal diamond (SCD). Photonic nanostructures, in our case SCD nanopillars on thin ( < 1 μm) platforms, are highly relevant for nanoscale sensing. The presented top-down procedure includes electron beam lithography (EBL) as well as reactive ion etching (RIE). Our method introduces a novel type of inter-layer, namely silicon, that significantly enhances the adhesion of hydrogen silsesquioxane (HSQ) electron beam resist to SCD and avoids sample charging during EBL. In contrast to previously used adhesion layers, our silicon layer can be removed using a highly-selective RIE step, which is not damaging HSQ mask structures. We thus refine published nanofabrication processes to ease a higher process reliability especially in the light of the advancing commercialization of SCD sensor devices.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Electron beam lithography; HSQ; Inductively coupled-reactive ion etching (ICP-RIE); Single-crystal diamond; Top-down nanofabrication